Wwox Deficiency Causes Downregulation of Prosurvival ERK Signaling and Abnormal Homeostatic Responses in Mouse Skin - Chou, Ying-Tsen; Lai, Feng-Jie; Chang, Nan-Shan; Hsu, Li-Jin (Frontiers in Cell and Developmental Biology, 2020)
Deficiency of tumor suppressor WW domain-containing oxidoreductase (WWOX) in humans and animals leads to growth retardation and premature death during postnatal developmental stages. Skin integrity is essential for organism survival due to its protection against dehydration and hypothermia. Our previous report demonstrated that human epidermal suprabasal cells express WWOX protein, and the expression is gradually increased toward the superficial differentiated cells prior to cornification. Here, we investigated whether abnormal skin development and homeostasis occur under Wwox deficiency that may correlate with early death. We determined that keratinocyte proliferation and differentiation were decreased, while apoptosis was increased in Wwox-/- mouse epidermis and primary keratinocyte cultures and WWOX-knockdown human HaCaT cells. Without WWOX, progenitor cells in hair follicle junctional zone underwent massive proliferation in early postnatal developmental stages and the stem/progenitor cell pools were depleted at postnatal day 21. These events lead to significantly decreased epidermal thickness, dehydration state, and delayed hair development in Wwox-/- mouse skin, which is associated with downregulation of prosurvival MEK/ERK signaling in Wwox-/- keratinocytes. Moreover, Wwox depletion results in substantial downregulation of dermal collagen contents in mice. Notably, Wwox-/- mice exhibit severe loss of subcutaneous adipose tissue and significant hypothermia. Collectively, our knockout mouse model supports the validity of WWOX in assisting epidermal and adipose homeostasis, and the involvement of prosurvival ERK pathway in the homeostatic responses regulated by WWOX.